MEKANISME SURVIVAL DAN MODAL SOSIAL PEDAGANG BERSTATUS JANDA DI PASAR SINJAI - Nurlina Subair; Andi Alim; Alimin Alwi (UNIVERSITAS SEBELAS MARET (UNS), 2022)
Single parenting is a phenomenon where mothers take care of and raise their children without the help of their partners. Meanwhile, the perspective of the surrounding community still sees a woman left by her husband, dead or living lightly or underappreciated. The purpose of this study was to determine the survival mechanism and the form of social capital of merchant widows in the Sinjai Central Market in improving the household economy. To find facts, the descriptive qualitative method is an option. The target of this research is people who are widows and work as traders in the Sinjai Central Market. Informants were selected by purposive sampling. Data were collected using participatory observation techniques, in-depth interviews and documentation studies. The analysis technique is carried out starting with data collection, data reduction, data presentation and conclusion. The results of the study found that the survival mechanism or survival strategy carried out by the widow of the merchant was to take action to suppress the cost of existing food needs; Taking action by involving family members in making a living and opening a salon business as an additional job; Take action to find additional work such as being padderos (harvest labour/slasher) and sharecroppers (farm labour). In addition, there are several actions taken that are not included in the framework of James Scott's theoretical analysis, such as committing criminal acts and saving activities. The form of social capital for merchant widows in earning a living so that they can increase their income is by joining lottery club groups in the market and their respective villages, borrowing (debt) and cooperation. All examples of forms of social capital carried out by merchant widows are closely related or inseparable from the network they have, the norms that apply in society and the trust between fellow traders or the community.Keywords: Survival Mechanism, Widow Trader, Social Capital AbstrakSingle parent merupakan fenomena sang ibu mengasuh dan membesarkan anak-anak mereka sendiri tanpa bantuan dari pasangannya. Sedangkan perspektif masyarakat sekitar masih memandang seorang perempuan ditinggal suami mati atau hidup dengan remeh atau kurang dihargai. Tujuan penelitian ini untuk mengetahui mekanisme survival dan bentuk modal sosial janda pedagang di Pasar Sentral Sinjai dalam meningkatkan perekonomian rumah tangganya. Untuk menemukan fakta maka metode kualitatif deskriptif sebagai pilihan. Sasaran penelitian ini adalah orang yang merupakan janda dan berprofesi sebagai pedagang di Pasar Sentral Sinjai. Informan dipilih dengan cara purposive sampling. Data dikumpulkan dengan teknik observasi partisipatif, wawancara mendalam serta studi dokumentasi. Teknik penganalisisan dilakukan berawal dengan pengumpulan data, reduksi data, penyajian data dan penarikan kesimpulan. Hasil penelitian menemukan bahwa upaya mekanisme survival atau strategi bertahan hidup yang dilakukan janda pedagang yaitu melakukan tindakan penekanan terhadap biaya kebutuhan pangan yang ada; Melakukan tindakan dengan melibatkan anggota keluarga dalam mencari nafka dan membuka usaha salon sebagai tambahan pekerjaan; Melakukan tindakan mencari pekerjaan tambahan seperti menjadi padderos (buruh panen/penebas) dan petani penggarap (buruh tani). Selain itu, ada beberapa tindakan di lakukan tidak masuk kerangka analisis teori James Scott seperti melakukan tindakan kriminalitas dan aktifitas menabung. Bentuk modal sosial janda pedagang dalam mencari nafkah sehingga bisa meningkatkan pendapatannya yaitu dengan bergabung dengan kelompok arisan di pasar maupun di desa masing-masing, meminjam (berutang) dan gotong royong. Semua contoh bentuk modal sosial yang dilakukan janda pedagang erat kaitannya atau tidak lepas dari jaringan yang dimiliki, norma yang berlaku dalam masyarakat dan kepercayaan antar sesama pedagang atau masyarakat.Kata Kunci: Mekanisme Survival, Pedagang Berstatus Janda, Modal Sosial